One foot out the door: limb function during swimming in terrestrial versus aquatic turtles. (31st January 2017) - Young, Vanessa K Hilliard; Vest, Kaitlyn G.; Rivera, Angela R. V.; Espinoza, Nora R.; Blob, Richard W.
Abstract : Specialization for a new habitat often entails a cost to performance in the ancestral habitat. Although aquatic lifestyles are ancestral among extant cryptodiran turtles, multiple lineages, including tortoises (Testudinidae) and emydid box turtles (genus Terrapene ), independently specialized for terrestrial habitats. To what extent is swimming function retained in such lineages despite terrestrial specialization? Because tortoises diverged from other turtles over 50 Ma, but box turtles did so only 5 Ma, we hypothesized that swimming kinematics for box turtles would more closely resemble those of aquatic relatives than those of tortoises. To test this prediction, we compared high-speed video of swimming Russian tortoises ( Testudo horsfieldii ), box turtles ( Terrapene carolina ) and two semi-aquatic emydid species: sliders ( Trachemys scripta ) and painted turtles ( Chrysemys picta ). We identified different kinematic patterns between limbs. In the forelimb, box turtle strokes most resemble those of tortoises; for the hindlimb, box turtles are more similar to semi-aquatic species. Such patterns indicate functional convergence of the forelimb of terrestrial species, whereas the box turtle hindlimb exhibits greater retention of ancestral swimming motions.